The Practice of Presidential Autocratic Legalism in Executive Regulations for National Strategic Projects: Praktik Presidential Autocratic Legalism dalam Peraturan Eksekutif untuk Proyek Strategis Nasional - Saleh, Muhamad; Perdana, Muhammad Anugerah (Jurnal Konstitusi, 2025)
The study of autocratic legalism in executive regulations analyses two main aspects. First, the study examines how the president applies autocratic legalism in the issuance of executive regulations related to the National Strategic Projects (PSN). Second, it aims to design an effective system of checks and balances to manage executive regulations. Using a mixed doctrinal and empirical approach within a socio-legal framework, the findings from the PSN case study indicate that the practice of autocratic legalism observed at the legislative level is also evident in executive regulations, where the president plays a dominant role, resulting in the usurpation of some of the legislative functions of the House of Representatives and giving rise to a character of presidential authoritarianism. Additionally, several important points emerge: (a) the hegemony of executive regulations that disregards provisions in sectoral laws; (b) executive hyper-regulation, where the Executive directs approximately 61.22% of the implementing regulations of the Job Creation Law (omnibus law) to supporting the priorities of National Strategic Projects; (c) the emergence of conflicts of interest due to the possibility of private entities proposing National Strategic Projects; and (d) a significant neglect of environmental and social impacts.